Body Mass Index of Pregnant Women and Anemia in Children Aged 6-12 Months in Sidodadi, Pondok Kelapa, Central Bengkulu Regency, Bengkulu, Indonesia - Agustina, Tri; Erlinawati, Noor Diah; Fajariyah, Sri Utami (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2025)
Highlights: There is still a medium incidence of anemia in infants aged 6-12 months. Pregnant women with high BMI and excessive weight gain are more likely to have anemic infants. Nutrient intake for pregnant women and infants is essential to determining the incidence of anemia.   Abstract Introduction: Children are more likely to experience psychological and motor developmental difficulties if they or their mothers have anemia. This study aimed to describe the maternal body mass index (BMI) during gestation and the prevalence of anemia in children aged 6-12 months. Methods: This descriptive study was conducted during integrated service post (posyandu) activities in Sidodadi, Pondok Kelapa, Central Bengkulu Regency, Bengkulu, Indonesia, in February 2023, involving the collection of Maternal and Child Health Handbook (KIA) records and blood sampling on children. A total sample of 35 pairs of mothers and children was collected. The data in this study were analyzed using the Fisher test, with a p-value of <0.05 indicating an association between the variables tested, and employing the International Business Machines Corporation (IBM) Statistical Package for the Social Sciences (SPSS) version 26.0 for Windows. Results: Underweight mothers had one child with anemia (2.9%), mothers who had normal BMI had five children with anemia (14.3%), overweight mothers had two children with anemia (5.7%), whilst obese mothers had four children with anemia (11.4%). Fisher’s exact test results showed no significant difference in the anemia status of children between underweight to normal BMI mothers, as well as when compared to overweight to obese mothers, with a p-value of 0.261 or >0.05. Conclusion: There was no significant difference in the anemia status of children with underweight up to normal maternal BMI mothers and overweight up to obese mothers.